Combining Uranium, Boron, and Strontium Isotope Ratios (234U/238U, δ11B, 87Sr/86Sr) to Trace and Quantify Salinity Contributions to Rio Grande River in Southwestern United States - Garcia, Sandra; Louvat, Pascale; Gaillardet, Jerome; Nyachoti, Syprose; Ma, Lin (Frontiers in Water, 2021)
In semi-arid to arid regions, both anthropogenic sources (urban and agriculture) and deeper Critical Zone (groundwater with long flow paths and water residence times) may play an important role in controlling chemical exports to rivers. Here, we combined two anthropogenic isotope tracers: uranium isotope ratios (234U/238U) and boron isotope ratios (δ11B), with the 87Sr/86Sr ratios to identify and quantify multiple solute (salinity) sources in the Rio Grande river in southern New Mexico and western Texas. The Rio Grande river is a major source of freshwater for irrigation and municipal uses in southwestern United States. There has been a large disagreement about the dominant salinity sources to the Rio Grande and particularly significant sources are of anthropogenic (agriculture practices and shallow groundwater flows, groundwater pumping, and urban developments) and/or geological (natural groundwater upwelling) origins. Between 2014 and 2016, we collected monthly river samples at 15 locations along a 200-km stretch of the Rio Grande river from Elephant Butte Reservoir, New Mexico to El Paso, Texas, as well as water samples from agricultural canals and drains, urban effluents and drains, and groundwater wells. Our study shows that due to the presence of localized and multiple salinity inputs, total dissolved solids (TDS) and isotope ratios of U, B, and Sr in the Rio Grande river show high spatial and temporal variability. Several agricultural, urban, and geological sources of salinity in the Rio Grande watershed have characteristic and distinguishable U, Sr, and B isotope signatures. However, due to the common issue of overlapping signatures as identified by previous tracer studies (such as δ18O, δD, δ34S), no single isotope tracer of U, Sr, or B isotopes was powerful enough to distinguish multiple salinity sources. Here, combining the multiple U, Sr, and B isotope and elemental signatures, we applied a multi-tracer mass balance approach to quantify the relative contributions of water mass from the identified various salinity end members along the 200-km stretch of the Rio Grande during different river flow seasons. Our results show that during irrigation (high river flow) seasons, the Rio Grande had uniform chemical and isotopic compositions, similar to the Elephant Butte reservoir where water is stored and well-mixed, reflecting the dominant contribution from shallow Critical Zone in headwater regions in temperate southern Colorado and northern New Mexico. In non-irrigation (low flow) seasons when the river water is stored at Elephant Butte reservoir, the Rio Grande river at many downstream locations showed heterogeneous chemical and isotopic compositions, reflecting variable inputs from upwelling of groundwater (deeper CZ), displacement of shallow groundwater, agricultural return flows, and urban effluents. Our study highlights the needs of using multi-tracer approach to investigate multiple solutes and salinity sources in rivers with complex geology and human impacts.